Explorando os principais fatores que afetam o comportamento do consumidor de food delivery: uma proposta de modelo integrativo - Maekawa, Rafael (2023)
The pandemic has changed the habits of people across the planet, triggering a new process of deeper change in food buying and selling chains, in line with the needs imposed by contingency and social distancing. Faced with this sudden scenario, restaurants and bars had to reinvent themselves and food delivery became a matter of survival. Given this context, this work aimed to identify what are the main factors that affect the behavior of consumers of food delivery applications. To answer the research question, the Systematic Literature Review (SLR), meta-analysis and empirical analysis of the factors that impact consumer behavior were used. With the results from the SLR, this work identified 78 factors that impact behavior, but the results of the meta-analysis identified that 30 factors showed moderate or strong correlation with the stages of consumer behavior. With the results of the meta-analysis, this work was also able to propose four new theoretical models, in addition, through observation and a documental analysis, the present work brought an empirical view of what is being applied in the largest food delivery application in the Brazilian market. From an academic perspective, the RSL and the meta-analysis analyzed and ranked, within the relevant literature on food delivery services, the main factors and theories about consumer behavior. From the corporate point of view, this research presents an empirical diagnosis of the Brazilian context of food delivery. With real examples of the iFood application, market leader in Brazil, managers and analysts working in the food delivery sector or related sectors will be able to use the practical manual as a reference for future applications or launching new products.